Synthesis and reactivity of complexes containing a group 13-group 11 bond - McManus, CB (2022)
This thesis describes the synthesis of heterobimetallic complexes which contain an unsupported bond between a group 13 and a group 11 metal (Cu, Ag, Au). While the primary focus is on bonds to aluminium, which are lesser known, the analogous gallium-coinage metal compounds are also investigated as a point of comparison. The methodology used in this work makes use of the first of a new class of nucleophilic aluminium ‘aluminyl’ anions, K2[(NON)Al]2 (NON = 4,5-bis(2,6-diisopropylanilido)-2,7-di-tert-butyl-9,9-dimethylxanthene), which is reacted with group 11 electrophiles of the form R3PMI (R = Ph, tBu, Cy) in a salt metathesis reaction. This approach gives access to rich structural variety, producing bimetallic complexes of the form (NON)AlMPtBu3, a 2:1 di(aluminyl)cuprate system, K[Cu{Al(NON)}2], and trimetallic iodide bridged complexes, (NON)Al(MPPh3)2I. These compounds are characterised by X-ray crystallography and multinuclear NMR, with spectroscopic comparisons to the heavier congeners (prepared using the gallyl reagent K2[(NON)Ga]2 giving insight into the properties of the aluminyl fragment as a metalloligand.